(untitled) (ENTHYMEMA, 2011)
The legal publishing industry, instead of adopting uniform editorial criteria, has been recently looking for eccentric modalities, apparently with the aim of saving on the individual typographical character. While the digitalization of systems could have expanded the range of communicative modalities, if we look at the publishers perspective, this has been rather reduced. In this context the expressive autonomy of the author remain intact in a way that is neither justified by an actual saving, nor by other nobler needs. The online publishing can definitely help in overcoming these problems.